Fetal and early postnatal development of the porcine tonsils of the soft palate - Suzuki, Shunichi (Exp Anim, 2019)
Tonsils are mucosa-associated lymphoid tissues located at the openings of the gastrointestinal and respiratory tracts, which play a key role in the surveillance of inhaled or ingested pathogens and can concurrently be reservoirs of infectious agents. Therefore, tonsils are important for the immunology and hygiene management of domestic animals, including pigs. However, the process of their fetal developmental has been poorly described, at least in part, because rodents lack tonsils. Therefore, we performed a histological analysis of porcine tonsils of the soft palate from 60 to 100 days of gestation (DG) and from 2 to 14 days post partum (DP). This analysis showed that lymphoid aggregations first appear at DG65, gradually develop during the fetal stage, and expand after birth. In addition, the mRNA expression of chemokine genes involved in lymphoid aggregation and localization was analyzed. CCL19 expression showed the most marked increase and a sharp peak after birth. CCL21 expression changed moderately but showed an interesting bimodal pattern. CXCL13 expression steadily increased throughout the study period. Thus, we demonstrated the mRNA expression of chemokine characteristically changed accompanying tonsillar development.